2015
DOI: 10.1021/acs.energyfuels.5b00573
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Oxide-Promoted Anaerobic Process of the Aquatic Plant of Curly Leaf Pondweed

Abstract: The technique of producing methane with lignocellulosic biomass as feedstock has been used worldwide. In the current study, three types of iron oxides, including goethite, hematite, and magnetite, were used to improve methane production from the aquatic plant curly leaf pondweed. In comparison to the control, hydrolysis efficiency of the aquatic plant in reactors with iron oxides was increased from 31.4 ± 0.1% to a higher level, which varied between 49.1 ± 4.6 and 74.1 ± 4.1%, and the accumulated methane produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Jiang et al reported a significantly promoted methanogenesis by the addition of poorly crystalline akaganeite, proposing a mechanism that this kind of iron oxide, which functioned as an electron flow medium, could accelerate the syntrophic metanogenesis of acetate-oxidizing bacteria and methanogenic archaea. Ma et al and Tan et al also verified that iron oxide minerals can be used as an effective supplementation to enhance methane yields from AD of different biomasses.…”
Section: Introductionmentioning
confidence: 95%
“…Jiang et al reported a significantly promoted methanogenesis by the addition of poorly crystalline akaganeite, proposing a mechanism that this kind of iron oxide, which functioned as an electron flow medium, could accelerate the syntrophic metanogenesis of acetate-oxidizing bacteria and methanogenic archaea. Ma et al and Tan et al also verified that iron oxide minerals can be used as an effective supplementation to enhance methane yields from AD of different biomasses.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, magnetite particles, as conductive materials, have been applied to the waste treatment process. Ma et al 7 also found that magnetite could improve the degradation efficiency of an aquatic plant, curly-leaf pondweed. Moreover, the effects of magnetite on the anaerobic co-digestion of pig manure and wheat straw proved that magnetite could enhance methane production and cellulase activity.…”
Section: Introductionmentioning
confidence: 98%
“…Biochar was reported to be able to accelerate the IET rate with cells separately attached to the surface of biochar, suggesting that electrons were likely conducted through the biochar (Chen et al, 2014b). Many studies demonstrated that the methanogenesis process was significantly accelerated in the presence of iron oxide by promoting the DIET process (Cruz Viggi et al, 2014;Kato et al, 2012b;Li et al, 2015a;Ma et al, 2015). Beside iron oxide, carbon nanotubes (CNTs) in the methanogenic sludge of anaerobic wastewater treatment systems induced much faster methane production and substrate utilization rates (Li et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%